2005
DOI: 10.1016/j.tcb.2005.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Plant organellar protein targeting: a traffic plan still under construction

Abstract: It has long been understood that specific features of a protein and its corresponding import apparatus dictate the behavior of mitochondrial proteins in their intracellular targeting behavior. In plants, the process by which proteins are directed to organelles has been influenced uniquely by the introduction to the cell of plastids. Parallel functions carried out within the mitochondrion and plastid permit the sharing of proteins and emergence of mechanisms to facilitate dual-targeting of the nuclear-encoded p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 51 publications
1
62
0
5
Order By: Relevance
“…In recent years, it has become clear that a number of proteins encoded by nuclear genes are dual targeted, with the chloroplasts/mitochondria being the most common dual destinations (Silva-Filho, 2003;Mackenzie, 2005). Dual plastid/mitochondrion targeting can be achieved either with twin presequences or with an ambiguous presequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has become clear that a number of proteins encoded by nuclear genes are dual targeted, with the chloroplasts/mitochondria being the most common dual destinations (Silva-Filho, 2003;Mackenzie, 2005). Dual plastid/mitochondrion targeting can be achieved either with twin presequences or with an ambiguous presequence.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of examples have been described in which proteins are dual targeted to both the chloroplast and mitochondrion (Small and Peeters, 2001;Mackenzie, 2005). Dual targeting is typically accomplished by the presence of tandem chloroplastic and mitochondrial targeting sequences or else by the presence of an ambiguous presequence that is recognized by the import apparatus of both organelles.…”
Section: Dual Targeting Of Fd-gogat To the Mitochondria In Addition Tmentioning
confidence: 99%
“…Indeed, several studies have demonstrated that translational regulation could occur at various levels. These include alternative translation initiation with one transcript producing two proteins targeted to different organelles, microRNA (miRNA)-mediated repression of translation by pausing ribosomes or accelerating ribosome drop-off, and lower reinitiation efficiency of main open reading frames (mORFs) by the translation of upstream open reading frames (uORFs) in the 59 untranslated region (UTR) (reviewed in Morris and Geballe, 2000;Mackenzie, 2005;Fabian et al, 2010;Huntzinger and Izaurralde, 2011). To fully understand translational regulation, we need to measure the dynamic positional information and abundance of translating ribosomes on a transcript.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples exist of plant genes encoding proteins targeted to both mitochondria and plastids (Mackenzie, 2005). However, one might hypothesize that the process of protein dual targeting is subject to some degree of cellular regulation to control relative protein stoichiometries in different tissues.…”
Section: Introductionmentioning
confidence: 99%